Analisis Putusan Hakim Terhadap Kasus No. 32/PDT.G/2019/PA.PANDAN Tentang Pemaksaan Hubungan Seksual Terhadap Isteri Yang Sedang Haid - Ikhwanuddin Harahap, Adelina Widiya Arnaz & Fatahuddin Aziz Siregar & (Jurnal El-Thawalib, 2020)
Law Number 1 of 1974 concerning Marriage in number 4 letter e with the editorial stating that in principle the Marriage Law adheres to the principle of complicating divorce which allows divorce to occur only if it is carried out before the Court and based on certain reasons (limitative reasons). Thus, all investigative activities in the Court or other activities in the Court relating to the settlement of divorce cases are one of the things that represent the principle of complicating the divorce. In this case, a wife is suing for her husband for divorce because the husband often asks to be served by his wife when her wife is menstruating, a husband constantly forces his will on his wife because his wife does not fulfill her husband's request, so a husband forces his wife to do it. sexual intercourse was forced and resulted in violence perpetrated by her husband. Therefore, this research will conduct a study on How the Judges of the Pandan Religious Court in deciding Case No. 32 / Pdt.G / 2019 / PA.Pandan